Public health response to methanol mass poisoning in the Czech Republic in 2012: a case study - Šejvl, Jaroslav; Barták, Miroslav; Gavurová, Beáta; Mašlániová, Miroslava; Petruželka, Benjamin; Rogalewicz, Vladimír; Zacharov, Sergej; Miovský, Michal (Central European Journal of Public Health, 2019)
OBJECTIVES: The study focuses on the 2012 methanol outbreak in the Czech Republic. The main goal of the present study was to apply analytical and descriptive tools to selected qualitative and quantitative processes related to the 2012 methanol outbreak in the Czech Republic. The secondary goal was to study and evaluate in detail their potential for creating integrated conceptual national policies aimed at eliminating the risk of methanol poisoning in the future. METHODS: The presented qualitative analysis focused on the content of documents published by Czech public authorities - the Ministry of Health, the Ministry of the Interior, the Czech Agriculture and Food Inspection Authority, and the Regional Public Health Authorities - as well as the content of the relevant legal regulations. Moreover, statistical data concerning the number of hospitalisations and deaths due to the methanol intoxication were used to provide a background to a detailed description of the relevant facts. RESULTS: In procedural terms, most of the analysed measures focused on a strongly restrictive regulation of sales, regular information channels designed to protect consumers on the national as well as international level, and elimination of further health and economic risks stemming from the dangerous alcoholic products that had already entered distribution networks. The health, social and economic consequences of such activities are quantified at a highly aggregated level. The analysed institutional ties are evaluated also in the context of international documents: the European Action Plan to Reduce Harmful Use of Alcohol 2012-2020 and the Global Strategy to Reduce Harmful Use of Alcohol, and their current potential for steering public policies is assessed. CONCLUSION: The analysis and evaluation of procedural activities carried out after the methanol outbreak have laid the foundations for a multidimensional study that can contribute to integrated national policy concepts aimed at preventing these and similar negative health, societal and economic consequences. Six years after the methanol outbreak, national and regional health policies have reflected no findings concerning the experience of patients whose health was impaired due to methanol, and the economic cost of the event has not been calculated. The quality of life of these patients has greatly decreased due to permanent or partial incapacity and serious upheavals of their and their families' economic and social conditions. This opens the question of researching and evaluating multiple aspects of health, social and economic impacts of harmful use of alcohol and setting up processes to mitigate these impacts.
Keywords: veřejná politika; Disease Outbreaks; Qualitative Research; methanol; otrava; Humans; Česká republika; lidé; epidemický výskyt choroby; Public Policy; Poisoning; kvalitativní výzkum; Czech Republic; Methanol